2014
DOI: 10.1097/mpa.0000000000000185
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Standardized Uptake Value on 18F-Fluoro-2-Deoxy-Glucose Positron Emission Tomography/Computed Tomography and Glucose Transporter-1 Expression Correlates With Survival in Invasive Ductal Carcinoma of the Pancreas

Abstract: ObjectivesThe purpose of this study was to assess the correlations among the maximum standardized uptake value (SUVmax) on 18F-fluoro-2-deoxy-glucose positron emission tomography/computed tomography (FDG-PET/CT); the expressions of glucose transporter 1 (GLUT-1), glucose transporter 3, and epidermal growth factor receptor (EGFR); as well as prognosis in patients with invasive ductal carcinoma of the pancreas.MethodsA total of 41 patients with surgically resected and histologically proven invasive ductal carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 25 publications
(40 reference statements)
1
17
0
Order By: Relevance
“…However, there are mixed reports on the utility of FDG-PET compared with CT, MRI, and endoscopic ultrasound techniques. The most useful aspect of FDG-PET for PDAC appears to be the strong correlation between levels of FDG uptake and tumor aggressiveness in terms of pathological grade (Ahn et al, 2014;Chen et al, 2016), prediction of distant metastasis (Shinoto et al, 2013), and survival (Chen et al, 2016;Kitasato et al, 2014;Lee et al, 2014;Yamamoto et al, 2015). The strongest critique against use of FDG-PET in PDAC is the observation that it is no more effective than conventional imaging techniques to diagnose early stage pancreatic cancer or to detect small metastases (Matsumoto et al, 2013;Rijkers et al, 2014).…”
Section: Metabolic Imagingmentioning
confidence: 99%
“…However, there are mixed reports on the utility of FDG-PET compared with CT, MRI, and endoscopic ultrasound techniques. The most useful aspect of FDG-PET for PDAC appears to be the strong correlation between levels of FDG uptake and tumor aggressiveness in terms of pathological grade (Ahn et al, 2014;Chen et al, 2016), prediction of distant metastasis (Shinoto et al, 2013), and survival (Chen et al, 2016;Kitasato et al, 2014;Lee et al, 2014;Yamamoto et al, 2015). The strongest critique against use of FDG-PET in PDAC is the observation that it is no more effective than conventional imaging techniques to diagnose early stage pancreatic cancer or to detect small metastases (Matsumoto et al, 2013;Rijkers et al, 2014).…”
Section: Metabolic Imagingmentioning
confidence: 99%
“…Measurement of steady state metabolite levels suggests that glucose concentrations are not significantly elevated in most PDAs compared to adjacent pancreatic tissue (29). Nevertheless, among PDAs, higher levels of glucose uptake and expression of the primary glucose transporter, GLUT1 (SLC21A), correlate with worse prognosis (41, 42). Moreover, alterations in glucose delivery and utilization are required for PDA tumorigenesis, and mutant KRAS serves as a major regulator of these processes.…”
Section: Glucose and Glutamine Metabolism In Pdamentioning
confidence: 99%
“…SUVmax in pancreatic cancer and non-small cell lung cancer (NSCLC), in which EGFR and P53 mutations are associated with tumor progression or chemotherapy resistance (16,17). Besides, several studies have reported the relationship between the SUVmax and some serum tumor biomarker levels in many kinds of cancers, such as CA19-9, CA72-4, and CEA (18)(19)(20).…”
Section: Suvmax Of 18 F-fdg Pet/ct Correlates To Expression Of Major mentioning
confidence: 99%